E-MODUL SUPLEMEN PEMBELAJARAN BAHASA INDONESIA BERBASIS KEARIFAN LOKAL PATI - Sa'adah Sa'adah; Lintang Kironoratri; M. Syafruddin Kuryanto (Journal Prakarsa Paedagogia, 2023)
This study aims to develop supplementary e-modules for Indonesian language learning based on local wisdom. Research and development (R&D) is used as a method in this study by applying the Borg and Gall model. The feasibility of the e-module is assessed by 3 validators, namely the media validator, the material validator, and the user validator. The subjects in this study were the IV grade students at SDN Tegalharjo 02, which consisted of 6 students. Collecting data using observation techniques, interviews, and questionnaires. The results of the study stated that the developed e-module was feasible to use, as evidenced by the validation score of media experts obtaining a proportion of 87.5%, which means it was feasible, material expert validation obtained a proportion of 84%, which meant it was feasible, and user validation obtained a proportion of 98.8 % which means good. So, e-modules are good to use as learning supplements.